2007
DOI: 10.1016/j.biopsych.2006.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin Neurons in the Entorhinal Cortex of Subjects Diagnosed With Bipolar Disorder or Schizophrenia

Abstract: Background-Growing evidence indicates that the entorhinal cortex (ECx) might be affected in schizophrenia (SZ) and bipolar disorder (BD). To test whether distinct interneuronal subpopulations might be altered, numbers of parvalbumin-immunoreactive (PVB-IR) neurons were measured in the ECx of BD and SZ subjects. These neurons play a pivotal role within ECx intrinsic circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 139 publications
(134 reference statements)
4
68
1
1
Order By: Relevance
“…In the hippocampal CA3 region of DGKβ KO mice, the number of parvalbumin-positive cells was decreased (vs. WT controls), which would increase the susceptibility of DGKβ KO mice to seizure. Interestingly, the number of parvalbumin positive interneuron is decreased in the hippocampus of patients with bipolar disorder, too [11,21,22]. We reported ealier that DGKβ KO mice display mania-like behavior [8], and others have reported that a splice variant at the COOH-terminal of DGKβ is related to bipolar disorder [23].…”
Section: Discussionmentioning
confidence: 66%
“…In the hippocampal CA3 region of DGKβ KO mice, the number of parvalbumin-positive cells was decreased (vs. WT controls), which would increase the susceptibility of DGKβ KO mice to seizure. Interestingly, the number of parvalbumin positive interneuron is decreased in the hippocampus of patients with bipolar disorder, too [11,21,22]. We reported ealier that DGKβ KO mice display mania-like behavior [8], and others have reported that a splice variant at the COOH-terminal of DGKβ is related to bipolar disorder [23].…”
Section: Discussionmentioning
confidence: 66%
“…Qualitative microscopic analyses of morphologic abnormalities as well as quantitative measurements of neuronal density revealed no significant differences between the schizophrenia and control groups, 39,40 which supports our result showing no significant differences in BDNF, trkB-TK+ or GAD 67 mRNA expression between individuals with schizo phrenia and unaffected controls in this region. However, a study by Pantazopoulos and colleagues 41 reported a decrease in parvalbumin-immunoreactive neurons within the superficial layers of the EC in individuals with bipolar disorder but not those with schizophrenia. This calcium-binding protein delineates inhibitory interneurons within the cortex and has revealed GABAergic abnormalities in the dorsolateral prefrontal cortex (DLPFC) and hippocampus in the major psychiatric disorders.…”
Section: Discussionmentioning
confidence: 95%
“…of this class of cells is reduced by over 10%Beasley and Reynolds, 1997; Beasley et al, 2002; Woo 492 et al, 2004; Chance et al, 2005; Todtenkopf et al, 493 2005;Wheeler et al, 2006;Pantazopoulos et al, 2007),494 compared to only three studies that reported the contradic-495 tory finding of an increase(Daviss and Lewis, 1995; Kalus 496 et al, 1997;Tooney and Chahl, 2004). A few of these stud-497 ies used the global marker glutamic acid decarboxylase 498 (GAD), the enzyme primarily responsible for synthesizing 499 GABA, but most used a mixture of markers for the 500 calcium-binding proteins parvalbumin, calretinin and cal-501 bindin, each of which tends to identify a partially separate 502 sub-population.…”
mentioning
confidence: 99%